Azzahra Humaira Setiawan Pengaruh Social Media Marketing Terhadap Keputusan Pembelian yang Dimediasi oleh Perceived Quality dan Green Perceived Value: Pendahuluan, Landasan Teori, Metodologi, Hasil dan Pembahasan, Penutup - HUMAIRA, AZZAHRA HUMAIRA SETIAWAN; Mohamad Rifqy Roosdhani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of Social Media Marketing on Purchasing Decisions mediated by Perceived Quality and Green Perceived Value among Gen Z in Jepara Regency. This research uses quantitative research. This study involved Gen Z, Jepara Regency residents who have bought and used Citra Body Lotion. This study used 121 samples which were processed using SEM PLS 4.0. The results show that Social Media Marketing (SMM) has a positive and significant effect on purchasing decisions. In the mediation analysis, the perceived quality variable did not show a significant mediating effect between SMM and purchasing decisions. In contrast, the green perceived value variable is proven to have a positive and significant mediating influence between social media marketing and purchasing decisions. There is a positive and significant effect of social media marketing on perceived quality, a positive and significant effect of social media marketing on green perceived value, an insignificant effect of perceived quality on purchasing decisions, a positive and significant effect of green perceived value on purchasing decisions.